Kali Kemit sebagai Garis Demarkasi Indonesia-Belanda Pasca Agresi Militer Belanda I di Kebumen Tahun 1947 - Apriliyan Tri Hastuti; Akhmad Arif Musadad; Nur Fatah Abidin (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2022)
This study aims to analyze: (1) The Armistice background of the Post-Military Aggression I in 1947, (2) Kali Kemit as the Indonesian-Dutch Demarcation Line in Post-Dutch Military Aggression I, (3) The Impact of Kali Kemit as the Indonesian-Dutch Demarcation Line in Post-Dutch Military Aggression I in 1947. The method used in this research is the historical method. Sources of data used in this study are primary sources and secondary sources. The research data were obtained through interviews with historical actors and witnesses, literature studies in the form of Dutch newspapers, direct observations at Kali Kemit, and documentation of historical actors' records. The results of this study indicate that: (1) The prolonged battle between the allies and the Dutch against Indonesia ended after the two parties agreed to a ceasefire. (2) The ratification of the Renville Negotiations led to a border agreement between Republic of Indonesia and Dutch. The border agreement was implemented in the southern part of Central Java by establishing Kali Kemit as the border between Republic of Indonesia and Dutch, so that the Dutch withdrew their defense line to the west of the Kali Kemit. (3) The impact caused by the results of the Renville Negotiations was the division of the territory in Kebumen into two parts with Kali Kemit being the boundary line, the transfer of troops from the enclave to the territory of the Republic of Indonesia, Kali Kemit being the initial target of the Dutch attack when they were about to continue their journey to Yogyakarta in December 1948.